Postawy nauczycielek i nauczycieli wychowania przedszkolnego wobec kształcenia na odległość w czasie pandemii COVID-19 - Jankowiak, Barbara; Jaskulska, Sylwia; Rybińska, Anna (Rocznik Pedagogiczny, 2020)
This research report presents results of a study on kindergarten teacher’s attitudes toward distance education during the COVID-19 pandemic and their associations with selected characteristics re- lated to the teacher’s profession. The tools that the teachers used for distance education were also described. 429 correctly completed surveys were collected. The most positive opinions concerned the development of one’s professional competencies, feeling positive emotions in the relationship with children and their parents. One of the worst assessed areas was those related to the possibility of supporting the social and emotional development of children. Most of the examined aspects of professional functioning, e.g. seniority, the location of the kindergarten, did not differentiate the attitudes. The differences mainly concerned teachers of special kindergartens, who in some aspects of attitudes (e.g. positive emotions towards this form of work) obtained lower results than teachers employed in other types of kindergartens.